The Application of Different Types of Diffusers for African Catfish (Clarias gariepinus) Culture in Biofloc Systems: Effects on Growth and Water Quality - Maulianawati, Diana; Kiing, Hendri; Dewi, Dena Pramita; Irawati, Heni; Amien, Muhammad (Journal of Aquaculture and Fish Health, 2024)
Applying biofloc technology in the intensive and extensive culture of Clarias gariepinus can improve water quality and be used to feed fish. Aeration systems were a critical unit supporting biofloc and water quality. This study's objective was assessment to various types of diffusers on the growth and water quality in a C. gariepinus culture. Two types of diffusers unit were prepared for the experiment, there are air tube diffuser (AT) and air stone diffuser (AS). Growth parameters, water quality, and volume of biofloc were observed within 30 days. The survival rate, weight gain, average body weight, and specific growth rate of C. gariepinus were higher in the tanks that used air tubes (98%, 485.29 %, 7.52 g, 5.89%) than in the tanks that used air stones (92 %, 385.94 %, 5.98 g, 5.23%). The volume of biofloc range from 5.40-18.80 ml/L in AT tanks and 4.60-14.00 ml/L in AS tanks. There is no significant difference (p > 0.05) in water quality parameters and FCR value. However, using the air tube diffuser showed better results with the growth performance, survival rate, and formation of biofloc.